Gastroesophageal Reflux after Repair of Esophageal Atresia - Tovar, J. A.; Fragoso, A. C. (European Journal of Pediatric Surgery, 2013)
Background and Aims Gastroesophageal reflux (GER) is extremely frequent in patients with esophageal atresia and tracheoesophageal fistula (EA/TEF). It is often refractory to antireflux medication and requires antireflux surgery. The reasons for this close association, the dangers of persistent GER, and the indications, technical aspects, and pitfalls of antireflux operations in these patients are examined in the present study.Methods The literature and summary of a large institutional experience of the authors were reviewed.Results The esophagus is permanently defective in EA/TEF patients even when successful repair, sometimes under tension, has been achieved. Extrinsic and intrinsic innervations are abnormal and consequently, motor function and sphincters are defective. The result is that close to one half of these patients overall suffer chronic GER that leads often to Barrett esophagus. Fundoplication becomes necessary in more than 40% of them, particularly in cases of with refractory anastomotic stenoses and in those with pure and long-gap EA/TEF. In the long run, the risks of esophageal carcinoma are 50-fold higher in EA/TEF survivors than in the population at random. On the contrary, fundoplication is anatomically difficult to perform and it fails in one-fifth of these children due to the persistence of the conditions that facilitate GER in them.Conclusions GER is extremely frequent in patients treated for EA/TEF because of serious structural and functional deficiencies. It is refractory to medical treatment and often requires antireflux surgery. However, the high rates of wrap failure invite close follow-up in all cases and reoperation or other measures whenever necessary.
Keywords: esophageal atresia; tracheoesophageal fistula; long-gap; elongation; gastroesophageal reflux; stenosis; fundoplication